Green-Tourism-Based Tourism Development Model In Bromo Tengger Semeru National Park (TNBTS) in Tosari District, Pasuruan Regency, East Java - Wahyudi, Setyo Tri; Badriyah, Nurul; Sari, Kartika; Nabella, Rihana Sofie Nabella; Radeetha, Radeetha (Graduate School, Universitas Brawijaya, 2024)
Tourism is one of the leading sectors that makes a major contribution to the Indonesian economy, including in the Bromo Tengger Semeru National Park (TNBTS) area, Tosari District, Pasuruan Regency, East Java. Throughout 2022, the number of visitors to TNBTS is expected to increase rapidly, which will also lead to an increase in non-tax state income. However, the increase in the number of visitors not only has a positive influence but also has a negative impact, mainly related to environmental concerns. Some of the problems that arise include climate change, socio-cultural degradation, and damage to ecosystems. Sustainable tourism through Green Tourism is an important component for achieving balanced tourism, benefiting both the economy and the environment. Therefore, this research aims to develop a Green-Tourism model in TNBTS. The method used in this research is a mixed-methods approach, employing a SWOT analysis methodology. The research results indicate that local communities and stakeholders can implement a green tourism strategy based on local participation and incorporating local culture, which can increase employment opportunities to absorb labor from rural communities and mitigate the current trend of urbanization.